External Peer-Review Models in Australian Accounting Schools: Current Status and Perceived Effectiveness - Syed Fahad Ashraf; Trevor David Wilmshurst; Seedwell T.M. Sithole; Claire Horner (Australasian Accounting, Business and Finance Journal, 2024)
This study examines the current landscape of External Peer-Review Models (EPRMs) in Australian Accounting Schools, providing insights on their prevalence and perceived efficacy. Adopting a theoretical framework rooted in legitimacy theory, the research investigates whether accounting schools align their practices with societal norms, particularly in response to changing regulatory environments. Utilising a qualitative approach, interviews were conducted with 16 participants from both AACSB-accredited and non-accredited institutions in Victoria and New South Wales. Findings reveal diverse responses to EPRMs, with key findings emphasizing the importance of closing the loop in the Assurance of Learning cycle, calibration of learning standards, anonymity, credibility, prolonged engagement of external peers, and strategic partnerships with benchmarking institutions. Theoretical implications emphasize the role of EPRMs in assuring learning standards and maintaining legitimacy. This research contributes valuable insights for policymakers, educators, and stakeholders in understanding the current state and perceived effectiveness of EPRMs in Australian Accounting Education.
Keywords: External Referencing Process; External Peer Review Models; Measures of Effectiveness; Quality Assurance and Higher Education Standards Framework